2002
DOI: 10.1002/chin.200244137
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Preliminary Evaluation of Benzimidazole Derivatives as Antimicrobial Agents.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Recent studies have confirmed that its derivatives are effective against various strains of microorganisms [7][8][9][10][11][12][13][14][15][16]. The basis of a special interest of researchers toward benzimidazole derivatives has been 5,6-dimethylbenzimidazole, which is a fragment of cyanocobalamine (vitamin B 12 ) that is capable of inducing the growth of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that its derivatives are effective against various strains of microorganisms [7][8][9][10][11][12][13][14][15][16]. The basis of a special interest of researchers toward benzimidazole derivatives has been 5,6-dimethylbenzimidazole, which is a fragment of cyanocobalamine (vitamin B 12 ) that is capable of inducing the growth of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive biochemical and pharmacological studies have confirmed that benzimidazole molecules are effective against various strains of microorganisms [1][2][3][4][5][6][7][8]. Benzimidazoles are regarded as a promising class of bioactive heterocyclic compounds that exhibit a range of biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…benzyl)sulfanyl benzimidazole (BIM), 5) 5-methylbenzimidazole (5-Me-BIM), 6) benzoxazole (BOZ), 7) and some benzothiazole (BTZ) 8) …”
Section: Methodsmentioning
confidence: 99%
“…This increase of MDR-TB and emergence of XDR-TB provide the rationale to search for new antimycobacterial drugs. [2][3][4] Previously, we have reported the synthesis of 2-(substituted benzyl)sulfanyl derivatives of benzimidazole, 5) 5-methylbenzimidazole, 6) benzoxazole, 7) and benzothiazole 8) (XϭH, 4-NO 2 , 3-NO 2 , 2-NO 2 , 3,5-(NO 2 ) 2 , 2,4-(NO 2 ) 2 , 4-CN, 3-CN, only). General structure of these compounds is shown in Fig.…”
mentioning
confidence: 99%